Toxicological insights of Spike fragments SARS-CoV-2 by exposure environment: A threat to aquatic health? - Charlie-Silva, Ives; Araújo, Amanda P.C.; Guimarães, Abraão T.B.; Veras, Flávio P.; Braz, Helyson L.B.; de Pontes, Letícia G.; Jorge, Roberta J.B.; Belo, Marco A.A. [UNESP]; Fernandes, Bianca H.V.; Nóbrega, Rafael H. [UNESP]; Galdino, Giovane; Condino-Neto, Antônio; et al. (Elsevier, 2021)
The Spike protein (S protein) is a critical component in the infection of the new coronavirus (SARS-CoV-2). The objective of this work was to evaluate whether peptides from S protein could cause negative impact in the aquatic animals. The aquatic toxicity of SARS-CoV-2 Spike protein peptides derivatives has been evaluated in tadpoles (n = 50 tadpoles/5 replicates of 10 animals) from species Physalaemus cuvieri (Leptodactylidae). After synthesis, purification, and characterization of peptides (PSDP2001, PSDP2002, PSDP2003) an aquatic contamination has been simulated with these peptides during 24 h of exposure in two concentrations (100 and 500 ng/mL). The control group (“C”) was composed of tadpoles kept in polyethylene containers containing de-chlorinated water. Oxidative stress, antioxidant biomarkers and AChE activity were assessed. In both concentrations, PSPD2002 and PSPD2003 increased catalase and superoxide dismutase antioxidants enzymes activities, as well as oxidative stress (nitrite levels, hydrogen peroxide and reactive oxygen species). All three peptides also increased acetylcholinesterase activity in the highest concentration. These peptides showed molecular interactions in silico with acetylcholinesterase and antioxidant enzymes. Aquatic particle contamination of SARS-CoV-2 has cholinesterasic effect in P. cuvieri tadpoles. These findings indicate that the COVID-19 can constitute environmental impact or biological damage potential.
Keywords: Acetylcholinesterase; Amphibians; Coronavirus; Oxidative stress; SARS-Cov-2